2009
DOI: 10.4161/psb.4.4.7919
|View full text |Cite
|
Sign up to set email alerts
|

Plant NHX cation/proton antiporters

Abstract: Although physiological and biochemical data since long suggested that Na(+)/H(+) and K(+)/H(+) antiporters are involved in intracellular ion and pH regulation in plants, it has taken a long time to identify genes encoding antiporters that could fulfil these roles. Genome sequencing projects have now shown that plants contain a very large number of putative Cation/Proton antiporters, the function of which is only beginning to be studied. The intracellular NHX transporters constitute the first Cation/Proton exch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
149
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 225 publications
(155 citation statements)
references
References 116 publications
(219 reference statements)
5
149
0
1
Order By: Relevance
“…The discovery that vacuolar NHX proteins were capable of exchanging Na + and H + across the tonoplast led to the now widespread view that NHX proteins mediate this critical process in plants faced with a saline environment (Apse et al, 1999;Gaxiola et al, 1999;Blumwald, 2000;Quintero et al, 2000). However, this notion has been recently challenged based on the biochemistry of NHX proteins, which do not discriminate between Na + and K + or have a preference for K + transport (Venema et al, 2002;Rodríguez-Rosales et al, 2009;Jiang et al, 2010). The lack of correlative evidence between greater salt tolerance and the enhancement of Na + accumulation in different plant species overexpressing NHX proteins from various sources has also been pointed out (Rodríguez-Rosales et al, 2009;Jiang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The discovery that vacuolar NHX proteins were capable of exchanging Na + and H + across the tonoplast led to the now widespread view that NHX proteins mediate this critical process in plants faced with a saline environment (Apse et al, 1999;Gaxiola et al, 1999;Blumwald, 2000;Quintero et al, 2000). However, this notion has been recently challenged based on the biochemistry of NHX proteins, which do not discriminate between Na + and K + or have a preference for K + transport (Venema et al, 2002;Rodríguez-Rosales et al, 2009;Jiang et al, 2010). The lack of correlative evidence between greater salt tolerance and the enhancement of Na + accumulation in different plant species overexpressing NHX proteins from various sources has also been pointed out (Rodríguez-Rosales et al, 2009;Jiang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…However, this notion has been recently challenged based on the biochemistry of NHX proteins, which do not discriminate between Na + and K + or have a preference for K + transport (Venema et al, 2002;Rodríguez-Rosales et al, 2009;Jiang et al, 2010). The lack of correlative evidence between greater salt tolerance and the enhancement of Na + accumulation in different plant species overexpressing NHX proteins from various sources has also been pointed out (Rodríguez-Rosales et al, 2009;Jiang et al, 2010). Recently, Bassil et al (2011b) have shown that NHX1 and NHX2 proteins play a comparatively greater role in K + homeostasis than in Na + sequestration.…”
Section: Discussionmentioning
confidence: 99%
“…NHX-type Na + (K + )/H + exchangers are particularly important for the regulation of pH and ion homeostasis and have been implicated in a wide variety of physiological processes, including cell volume and expansion, osmotic adjustment, and stress responses (Rodríguez-Rosales et al, 2009;Bassil et al, 2012). They operate by exchanging luminal H + for Na + or K + and, therefore, regulate monovalent cation homeostasis in addition to functioning as "H + leaks" to fine-tune luminal pH by countering the acidity generated by the H + pumps (Orlowski and Grinstein, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The classic view is that this sequestration is achieved by tonoplast Na + /H + antiporters (Barkla et al, 1995;Flowers and Colmer, 2008), a process energized by both vacuolar H + pumps: ATPase (Ayala et al, 1996;Vera-Estrella et al, 1999;Wang et al, 2001) and pyrophosphatase (Parks et al, 2002;Vera-Estrella et al, 2005;Guo et al, 2006;Krebs et al, 2010). However, recent studies have added more complexity to the relationship between Na + /H + antiporters and vacuolar Na + sequestration, assigning a role to the transporter in the regulation of K + and H + homeostasis (for review, see Rodríguez-Rosales et al, 2009;Jiang et al, 2010; Bassil et al, 2011 (Yamaguchi et al, 2005). Consequently, other transporters, in addition to and different from NHX, are likely to be involved in vacuolar Na + sequestration.…”
mentioning
confidence: 99%